The Relationship Between Post-Traumatic Stress Disorder and Autism for Children Under 10 Years, Parents’ Perspective: A Case Control Study - Alhussaini, Ahmed Hassan; AL-Nasrawii, Maytham Salim (National Journal of Community Medicine, 2025)
Background: Post-Traumatic Stress Disorder (PTSD) occurs as a result of exposure to stressful events such as assaults, accidents, and disasters and poses a significant risk to a child’s mental health. Children with Autism Spectrum Disorder (ASD) are at a higher risk of developing PTSD compared to their neurotypical peers. This research aimed to investigate the correlation between PTSD & ASD in children under 10 years old. Methodology: A case-control study was conducted in Karbala Governorate from October 2024 to February 2025 among 80 autistic children and 160 non-autistics children. Data were obtained using a standardized questionnaire form of the Child PTSD Symptom Scale for DSM-V (CPSS-V SR) administered to cases and controls through direct interviews with the parents of the children. The questionnaire includes four domains (socio-demographic characteristics, family medical history, frightening or stressful events, and child PTSD symptom scale). Results: Indicated that autistic children were 4.33 times more likely to develop PTSD than non-autistic children with a confidence interval (1.264-14.859), which is statistically significant. Prevalence rates of probable PTSD were 10% among cases and 2.5% among controls. The probable PTSD diagnosis was higher among females (5.9%) than males (4.5%). The age group of 8-9 years showed the highest rate, accounting for 66.66% of probable PTSD cases. Stepwise regression analyses revealed several variables as highly significant predictors of PTSD diagnosis in children. Conclusion: Post-traumatic stress disorder was four times more likely to develop in autistic children compared to non-autistic children, with females being more susceptible than males, and older children at a greater risk of developing PTSD than their younger counterparts.